A comparative study of the tracheal tube fixation using band, adhesive and holder on the incidence of pressure ulcers in patients with head trauma - Ahmad Jafari Kheirabadi; Razieh Froutan; Seyed Reza Mazlom; Hosein Rohani Baygi (Tehran University of Medical Sciences, 2019)
Background & Aim: Brain injury is one of the most common traumas and the most important cause of death in traumatic events. Ventilated patients are susceptible to pressure ulcers caused by endotracheal tube fixation (ETF). The aim of the present study is to compare three methods of ETF (band, adhesive and holder) on the incidence of pressure ulcers in patients with head injury. Methods & Materials: This randomized clinical trial was performed in a hospital in Mashhad in 2017. A total of 108 hospitalized patients with head trauma were included in the study by convenience sampling. The patients were randomly divided into three groups of ETF using holder, band and adhesive. In three groups, the incidence of pressure ulcers caused by fixation method was assessed at 6, 12, 18, and 24 hours after the intervention. The grade of ulcer was measured by pressure grading scale (EPUAP/NPUAP). The data were analyzed using the SPSS software version 16. Results: The incidence of pressure ulcers at 6, 12, 18, and 24 hours after the intervention was significantly different in the three groups (P<0.05). At six and 12 hours after the intervention, the three groups had a grade one ulcer. However, after 18 hours, 10% in the adhesive group and band group and 24 hours after the intervention, 25% in the band group and 12.1% in the adhesive group had a grade 2 pressure ulcer, but this amount was 0% in the holder group. Conclusion: Use of holder rather than adhesive and band for ETF in mechanically ventilated patients causes less pressure ulcers. Clinical trial registry: IRCT20171015036800N1